Influência da deformação a frio e recozimento na textura cristalográfica e propriedades mecânicas dos aços inoxidáveis duplex UNS S31803 e UNS S32304 - Karina Aparecida Martins Barcelos Gonçalves (2015)
Due to its increasing use, the Duplex Stainless Steels have been intensely studied in recent years. DSS has a dualphase structure composed by ferrite and austenite. The presence of the two phases gives this type of steel superior properties than both ferritic and austenitic steels. This study evaluate of the influence of cold deformation and annealing in duplex stainless steels UNS S32304 (lean) and UNS S32205 / UNS S31803(standard) in relation to its behavior of texture and mechanical properties of the samples in the as-received, hardened and annealed conditions. Tensile test and hardness were performed. The crystallographic texture and quantification of phase were determined by: scanning electron microscopy (SEM) and high resolution scanning electron microscope (SEM-FEG FEI Quanta 200). Samples were analyzed by calculating the orientation distribuition function (ODF) and the orientation maps obtained by the technique of backscatter electron diffraction pattern (OIM_EBSD).